Monday

October 20, 2014

October 20, 2014

Posted by **shan** on Saturday, September 6, 2008 at 4:04pm.

(sinx/cosx)+ (1/cosx)=2cosx

(sinx+1)/cosx =2cosx

multiplying both sides by cosx

sinx + 1 =2cos^2x

sinx+1 = 2(1-sin^2x)

2sin^2x + sinx-1=0

(2sinx+1)(sinx-1)=0

x=30 x=270

but if i plug 270 back into the original equation i get undefined because tan 270 is undefined where did i go wrong?

**Answer this Question**

**Related Questions**

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...

Pre Calculus - Having trouble verifying this identity... cscxtanx + secx= 2cosx ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

Precalculus/Trig - I can't seem to prove these trig identities and would really ...

Trig - Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(...

math - solve each equation for 0=/<x=/<2pi sin^2x + 5sinx + 6 = 0? how do ...